hope im right but i think it 1 sorry if im wrong
Answer:
3(x² + 1) + 2
Step-by-step explanation:
(f ○ g)(x) = f(g(x))
Substitute x = g(x) into f(x), that is
f(x² + 1) = 3(x² + 1) + 2 ← is the equivalent statement
Answer:
The function g(x) has a greater x- intercept than the function f(x)
Step-by-step explanation:
The given formula ![A= 10 + ry](https://tex.z-dn.net/?f=%20A%3D%2010%20%2B%20ry%20)
Solve for y means we have to make y alone
\\
Add -10 on both sides, we get
![A - 10 = 10 -10 + ry \\A - 10 = 0 + ryA - 10 = ry](https://tex.z-dn.net/?f=%20A%20-%2010%20%3D%2010%20-10%20%2B%20ry%20%5C%5CA%20-%2010%20%3D%200%20%2B%20ry%3C%2Fp%3E%3Cp%3EA%20-%2010%20%3D%20ry%20)
As there is multiplication sign between r and y so to solve for y, divide both side by r
![\frac{A - 10}{r} = y\\\\y = \frac{A - 10}{r}](https://tex.z-dn.net/?f=%20%5Cfrac%7BA%20-%2010%7D%7Br%7D%20%3D%20y%5C%5C%5C%5Cy%20%3D%20%5Cfrac%7BA%20-%2010%7D%7Br%7D%20)
Answer:
Lots of steps and answers. Look at the picture.
Step-by-step explanation: